From Spiritual Vigilance to Tactical Ambush: A Socio-Cultural Recontextualization of Pesantren Ethos During the Second Military Aggression in Indonesia - Abdul Aziz, Faqih; Niam, Khoirun; Rozaqiy, Rohmat Robi'; Mutha'aliin, Ahmad Hikam; Miftahur R, Ziyad Ahmad (Universitas Islam Negeri Ar-Raniry, 2026)
Conventional military historiography concerning the Second Dutch Military Aggression (1948–1949) frequently separates General Sudirman’s guerrilla strategy from the spiritual dimensions of its agents, reducing spirituality to a mere ideological motivator. This article bridges the theoretical gap between military historiography and the sociology of religion gap by examining the sociological mechanisms through which the pesantren ethos was recontextualized into effective combat strategies. Addressing the ambiguity of